2021
DOI: 10.23937/2469-584x/1510079
|View full text |Cite
|
Sign up to set email alerts
|

Acute Cholecystitis: Comparison of Clinical Findings from Ultrasound and Computed Tomography

Abstract: Acute cholecystitis is a common surgical emergency, for which ultrasound (US) is the most common first-line diagnostic imaging test. Computed tomography (CT) is an alternative or complementary test for the assessment of acute cholecystitis. Acute cholecystitis is diagnosed based on clinical history and assessment, biochemical examination, and US findings. CT is considered only in case of unclear clinical symptoms or discrepant findings. We aimed to retrospectively compare the efficiency of CT and sonography fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 16 publications
1
1
0
Order By: Relevance
“…This finding appears to be similar to a previous study that found that the sensitivity of CT was significantly greater than US for detecting AC (85% versus 68%) [26]. When compared to the recent literature, Oda et al reported that CT had more sensitivity than US (85% versus 72%) [24]. Additionally, consistent with our results, Compared to US, CT was more sensitive (79% versus 92%) [27].…”
Section: Accuracy Of Us and Ctsupporting
confidence: 92%
See 1 more Smart Citation
“…This finding appears to be similar to a previous study that found that the sensitivity of CT was significantly greater than US for detecting AC (85% versus 68%) [26]. When compared to the recent literature, Oda et al reported that CT had more sensitivity than US (85% versus 72%) [24]. Additionally, consistent with our results, Compared to US, CT was more sensitive (79% versus 92%) [27].…”
Section: Accuracy Of Us and Ctsupporting
confidence: 92%
“…Therefore, US had a higher sensitivity than the CT scan but a lower specificity [6]. In addition, multiple studies found that CT is superior to US in diagnosing cholecystitis in adult patients undergoing emergency evaluation for RUQ pain and has the advantage of depicting acute non-gallbladder abnormalities [23][24][25]. Another study reported that US in pediatric patients with cholecystitis is less sensitive than in adults [21].…”
Section: Introductionmentioning
confidence: 99%